(untitled) (GEON Journal (Management, Organizations and Business), 2017)
Given the constant and decisive tax reforms, today, it is the social responsibility of the Public Accountant to analyze and inform the employer the true financial impact of electronic accounting, by virtue of which the Treasury, in order to achieve greater efficiency in its verification procedures and guarantee the veracity of the tax payment of the captive taxpayers, previously determined freely by the public accountant, currently the tax authority in Mexico, has imposed new bases eliminating now more than ever expenditures, investments and costs that in their opinion, are alien to the normal activity of the company, has reformed tax regimes, new forms of electronic invoicing, and some other provisions that affect the taxpayer captive considerably in the financial aspect. The objective is to comment on relevant financial aspects that impact the company with the obligation to keep the accounting electronically and the importance of this in business decision making. Due to the importance of electronic accounting, it is essential to budget operations of purchases, sales, expenses and utilities, in addition to reviewing and validating all digital documents observing fiscal requirements and having the respective files, as well as documenting operations, issuing and collecting the digital tax receipts of the economic transactions of purchase, sale, expenses and payroll in XML formats.